Dr Malcolm King Honoured at University of Alberta Annual General Meeting (Canadian Respiratory Journal)
On September 25, 2003, Dr Malcolm King, former Canadian Thoracic Society (CTS) President and member, was honoured by the University of Alberta (U of A) with the University of Alberta Board of Governors Award of Distinction for 2003. The following are highlights of an article written by Ryan Smith for ExpressNews.